Response of Corn (Zea mays L.) Growth and Production to Rice Husk Charcoal and Goat Manure Organic Fertilizer - Sulardi Sulardi; Sri Mahareni Sitepu (INFOKUM, 2026)
The decline in soil quality due to the continuous use of inorganic fertilizers is one of the main obstacles in increasing corn (Zea mays L.) productivity. The use of organic materials such as rice husk charcoal and goat manure organic fertilizer is an alternative to improve the physical, chemical, and biological properties of the soil so as to increase plant growth and yield. This study aims to analyze the effect of rice husk charcoal and goat manure organic fertilizer on the growth and production of corn plants and to evaluate the response of the two treatments. The study was conducted in Klambir Lima Village, Sunggal District, Deli Serdang Regency, North Sumatra, using a factorial Randomized Block Design (RBD) with two factors and three replications. The first factor was rice husk charcoal consisting of three levels, namely A₀ (0 kg/plot), A₁ (2 kg/plot), and A₂ (4 kg/plot), while the second factor was organic goat manure fertilizer consisting of four levels, namely K₀ (0 kg/plot), K₁ (2 kg/plot), K₂ (4 kg/plot), and K₃ (6 kg/plot). Data were analyzed using analysis of variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) at a significance level of 5%. The results showed that the administration of rice husk charcoal and organic goat manure fertilizer had a very significant effect on plant height, stem diameter, number of cobs per sample, number of cobs per plot, and cob weight per plot. The treatment of rice husk charcoal dose of 4 kg/plot (A₂) and organic goat manure fertilizer dose of 6 kg/plot (K₃) gave the best results in all observation parameters. The interaction of the two treatments did not show a significant effect. The use of rice husk charcoal and organic goat manure fertilizer has been proven to increase the growth and production of corn plants and has the potential to be applied as a cultivation technology that supports a sustainable agricultural system.